Analisis minat masyarakat dalam melakukan aktivitas olahraga di ruang terbuka - Safitri, Ayu Varida; Indarto, Pungki (Jurnal Porkes, 2023)
The problem in this study is the lack of public interest in carrying out sports activities in public open spaces is not yet known. This study aims to determine the level of public interest in carrying out sports activities in public open spaces. This research method uses survey research with a descriptive quantitative approach. Data was collected using an online questionnaire (goggle form). The population of all the people of Sidorejo District, Salatiga City, totaling 54,223 people and a sample of 150 samples using the accidental sampling technique. Data collection techniques in the form of observation, questionnaires and interviews. The research instruments are in the form of tests, questionnaires and questionnaires but must be tested for validity and reliability. The data analysis technique is a quantitative approach which is descriptive in percentage. The results of research on public interest in carrying out sports activities in open spaces in 2023 are categorized as high with a result of 78.78%. Calculations based on 81.91% intrinsic interest including very high category and 75.65% extrinsic interest including high category. In conclusion, people's interest in carrying out sports activities in open spaces is included in the high category.